Synthesis, molecular docking and DFT analysis of novel bis-Schiff base derivatives with thiobarbituric acid for α-glucosidase inhibition assessment - Gul, Saba; Jan, Faheem; Alam, Aftab; Shakoor, Abdul; Khan, Ajmal; AlAsmari, Abdullah F.; Alasmari, Fawaz; Khan, Momin; Bo, Li (Scientific reports, 2024)
A library of novel bis -Schiff base derivatives based on thiobarbituric acid has been effectively synthesized by multi-step reactions as part of our ongoing pursuit of novel anti-diabetic agents. All these derivatives were subjected to in vitro α-glucosidase inhibitory potential testing after structural confirmation by modern spectroscopic techniques. Among them, compound 8 (IC 50 = 0.10 ± 0.05 µM), and 9 (IC 50 = 0.13 ± 0.03 µM) exhibited promising inhibitory activity better than the standard drug acarbose (IC 50 = 0.27 ± 0.04 µM). Similarly, derivatives ( 5 , 6 , 7 , 10 and 4 ) showed significant to good inhibitory activity in the range of IC 50 values from 0.32 ± 0.03 to 0.52 ± 0.02 µM. These derivatives were docked with the target protein to elucidate their binding affinities and key interactions, providing additional insights into their inhibitory mechanisms. The chemical nature of these compounds were reveal by performing the density functional theory (DFT) calculation using hybrid B3LYP functional with 6-311++G(d,p) basis set. The presence of intramolecular H-bonding was explored by DFT-d3 and reduced density gradient (RGD) analysis. Furthermore, various reactivity parameters were explored by performing TD-DFT at CAM-B3LYP/6-311++G(d,p) method.